Bridging Gaps in Migrant Healthcare: CUAMM’s Experience from 13,103 Visits in Southern Italy - Cesare De Virgilio Suglia; Renato Laforgia; Marcella Schiavone; Anna Belfiore; Nicole Laforgia; Annalisa Saracino; Giovanni Putoto; Francesco Di Gennaro (Annals of Global Health)
Background: Agricultural migrant workers in rural Puglia, Italy, endure harsh living and working conditions that significantly affect their health and limit access to healthcare. This study evaluates their health status, explores systemic barriers to care, and evaluates the effectiveness of a mobile clinic model, identifying structural obstacles to healthcare access. Methods: Data were collected from 13,103 medical visits conducted between 2017 and 2023 by Doctors with Africa University College for Aspiring Missionary Doctors (CUAMM)’s mobile clinics operating in 12 informal settlements. Demographic, clinical, and socio‑health data from 2,537 unique patients were analyzed. Statistical methods, including multivariate regression, were employed to identify health trends and predictors of healthcare utilization. Results: The patient cohort was predominantly male (95.8%) and aged 19–45 years (83%). Work‑related musculoskeletal disorders were the most common diagnoses (27.3%), followed by respiratory infections (14.3%), dermatological conditions (12.1%), and dental problems (7.2%). Only 18% of patients had a residence permit, and 7% were registered with a general practitioner. Despite significant barriers, the average number of follow‑up visits per patient was 5.6, indicating trust in the mobile clinic model. Barriers included linguistic and cultural challenges, low health literacy, and irregular legal status. Mobile clinics provided not only primary medical care but also referrals and socio‑health guidance, effectively bridging healthcare gaps for this population. Conclusions: This study underscores the health vulnerabilities of migrant workers and the critical role of mobile clinics in addressing their needs. Integrating flexible care models with traditional systems, addressing labor exploitation, and improving living conditions are imperative. Collaborative efforts involving institutions, nongovernmental organizations (NGOs), and academia are essential to ensuring equitable, accessible, and sustainable healthcare for this marginalized population—leaving no one behind.